2007
DOI: 10.1186/ar2146
|View full text |Cite
|
Sign up to set email alerts
|

Biology and therapy of fibromyalgia. Stress, the stress response system, and fibromyalgia

Abstract: Stress is a state of disharmony, or threatened homeostasis. A stressor could have a psychological origin or a biological origin. Societies have become more intricate with industrialization, and modern individuals try to adapt to the new defiance by forcing their stress response system. The main component of the stress response network is the autonomic nervous system. The present article reviews current knowledge on autonomic dysfunction in fibromyalgia. Sympathetic hyperactivity has been consistently described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
0
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(185 citation statements)
references
References 32 publications
(29 reference statements)
7
168
0
10
Order By: Relevance
“…Dysfunctional ARs may provide a biologic explanation for some "somatization" symptoms. Different stress tests have shown that FM patients have orthostatic intolerance (3). Other studies have confirmed the relationship between low blood pressure and pain sensitivity (14,15).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Dysfunctional ARs may provide a biologic explanation for some "somatization" symptoms. Different stress tests have shown that FM patients have orthostatic intolerance (3). Other studies have confirmed the relationship between low blood pressure and pain sensitivity (14,15).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, mounting evidence suggests that FM is a sympathetically maintained neuropathic pain syndrome (3). Dysautonomia may also explain FM symptoms not related to pain.…”
Section: Conclusion Ar Gene Polymorphisms Are Related To the Risk Ofmentioning
confidence: 99%
“…1,2 In these patients, stress and pain may increase sympathetic nervous system (SNS) activity, and it has been reported that SNS function is changed in patients with FM. 6,7,12 On the other hand, arterial wall-stiffening process is significantly affected by SNS activity. 12 Increased sympathetic activity may change cardiovascular responses and cause endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…5 Additionally, sympathetic activity may increase in these patients due to pain and stress. 6,7 Previous studies have shown that sympathetic overactivity and autonomic dysfunction may contribute to the risk of endothelial dysfunction and cardiovascular disease in patients with FM.…”
mentioning
confidence: 99%
“…Many researchers have recently uncovered a link between the sympathetic nervous system and the stress reaction, especially in fibromyalgia patients. A "sympathetic hyperactivity" in the sympathetic portion of the autonomic nervous system as well as perturbation in the HPA axis (Griep, Boersma & Lentjes, 1998;Crofford et al, 1994;van Houdenhove, Egle & Luyten, 2005;van Houdenhove & Luyton, 2006) has been put forward as an explanation for both difficulties in pain relief and pain oversensitivity in fibromyalgia patients (Martinez-Lavin, 2007). This hyperactivity has its origins in disturbances of certain neurotransmitters (catecholamines).…”
Section: Introductionmentioning
confidence: 99%